Analisis Langkah - Langkah Polya dalam Menyelesaikan Soal Fungsi Kuadrat Ditinjau dari Perbedaan Gender - Efendi, Chaerunnisa Sumiatun Efendi; Husniatissibhi, Nisa; Hakim, Nur Afifi Al; Fadillah, Rezki; Novitasari, Dwi (Griya Journal of Mathematics Education and Application, 2025)
This study aims to analyze students’ problem-solving abilities in answering quadratic equation problems based on Polya’s problem-solving steps, viewed from gender differences. The research employed a descriptive qualitative approach involving 24 tenth-grade students from three high schools: SMAN 7 Mataram, SMAN 1 Labuapi, and SMAN 2 Mataram. The research instrument used was a Student Worksheet (LKPD) consisting of two sections: a guided problem with explicit Polya step prompts and an open-ended problem without guidance. The findings reveal that female students tended to complete the problems systematically and reflectively, with most of them falling into the “Very Good” category. In contrast, male students showed more variability in their responses, often demonstrating strength in operational stages but weakness in the reflection stage. The fourth step of Polya’s strategy—reviewing the result—was the most frequently overlooked by both gender groups. This study emphasizes the importance of explicitly and consistently applying Polya’s strategy in mathematics instruction to help develop logical, structured, and independent thinking patterns.